Complementizer agreement with coordinated subjects in Polish. Issue 1 (20th November 2018) - Citko, Barbara
Abstract : This paper examines complementizer and verbal agreement with coordinate subjects in Polish. It shows that while certain patterns are possible, others (logically equally plausible ones) are not. The possible patterns are: (i) Resolved Agreement on both the verb and the complementizer, (ii) mixed agreement (Resolved Agreement on the verb and First Conjunct Agreement on the complementizer, and (iii) sandwiched agreement (First Conjunct Agreement on the complementizer and Last Conjunct Agreement on the verb). The differences between Resolved Agreement and Single Conjunct Agreement are attributed to two distinct ways Agree can operate; either as a sequence of Singular Agree operations, or as one instance of Multiple Agree, with Multiple Agree yielding Resolved Agreement and Singular Agree requiring feature conflict resolution at PF.